Distribution Of Health Insurance Premiums Between The Public And Private Sectors (Latakia University Journal - Economic and Legal Sciences Series, 2020)
This study aims to study the distribution of health insurance premiums between the public and private sectors from 2006 to the first half of 2019 in the Syrian Arab Republic in order to know the growth rate of health insurance premiums and the percentage of health insurance premiums compared to the total insurance premiums of public and private insurance companies operating in Syria. The study also focused on the most important factors affecting on health insurance premiums and their suitability for increasing the costs of medical expenses provided. This study reached a set of results, the most important of which are: a decrease in the value of the premium for health insurance paid due to inflation during the study period, with health insurance premiums remaining constant before and during the war, which is (8000) SP by year. This affected the coverage percentages of health insurance companies and the employee's loss a part of the health services provided.